Is sarcopenia associated with depression? A systematic review and meta-analysis of observational studies - Chang, Ke-Vin; Hsu, Tsai-Hsuan; Wu, Wei-Ting; Huang, Kuo-Chin; Han, Der-Sheng (Age and ageing, 2017)
to explore whether sarcopenia is associated with depression. electronic literature databases from PubMed, Scopus, Embase and Google Scholar were searched. A systematic review and meta-analysis of observational studies was conducted. community and outpatient clinic. people with and without diagnoses of sarcopenia. outcome measures of depression. about 15 articles were included, 5 of which were retrieved for narrative review. The crude odds ratios (ORs) between sarcopenia and depression were extracted from the remaining 10 studies, 6 of which also included adjusted ORs. Sarcopenia was associated with depression without adjusting covariates (crude OR, 1.640; 95% confidence interval (CI), 1.247-2.155). After adjusting for potential confounders such as age, gender, cognitive performance and physical activity, sarcopenia still demonstrated a significant positive association with depression (adjusted OR, 1.821; 95% CI, 1.160-2.859). A stratified analysis showed that the studies that used bioelectrical impedance analysis for measurement of body composition tended to have an elevated association between sarcopenia and depression compared with those that used dual-energy X-ray absorptiometry or equation estimation. sarcopenia was independently associated with depression. The causal relationship between the two clinical conditions requires future validation with cohort studies.